Universal Design for Learning in Pre-K to Grade 12 Classrooms: A Systematic Review of Research. Issue 2 (3rd April 2017) - Ok, Min Wook; Rao, Kavita; Bryant, Brian R.; McDougall, Dennis
ABSTRACT: Some researchers have characterized Universal Design for Learning (UDL) as a promising framework to provide diverse students with access to the general education curriculum, but to what extent and how have UDL-based interventions fulfilled that promise? The purpose of this review was to analyze studies that investigated impacts of UDL-based instruction on academic and social outcomes for pre-K to grade 12 students. For the 13 studies that qualified for our review, we analyzed how researchers applied UDL principles as well as outcomes and efficacy of UDL-based interventions. Results of this analysis suggest that overall, UDL-based instruction has the potential to increase engagement and access to general education curriculum for students with disabilities, and improve students' academic and social outcomes. However, we found mixed results; the efficacy of UDL-based interventions varied considerably within and across many studies, with effect sizes ranging from small to large. In addition, we found that although authors noted that their interventions were UDL-based, there was considerable variance in how authors reported connections between specific UDL guidelines and components of their interventions.